Imperios en guerra, 1911-1923 - Gerwarth, Robert; Manela, Erez; Veuthey, Maysi (Pretérita, 2015)
Empires at War, 1911-1923 offers a new perspective on the history of the Great War, looking at the war beyond the generally-accepted 1914-1918 timeline, and as a global war between empires, rather than a European war between nation-states. The volume expands the story of the war both in time and space to include the violent conflicts that preceded and followed World War I, from the 1911 Italian invasion of Libya to the massive violence that followed the collapse of the Ottoman, Russian, and Austrian empires until 1923. It argues that the traditional focus on the period between August 1914 and November 1918 makes more sense for the victorious western front powers (notably Britain and France), than it does for much of central-eastern and south-eastern Europe or for those colonial troops whose demobilization did not begin in November 1918. The paroxysm of 1914-18 has to be seen in the wider context of armed imperial conflict that began in 1911 and did not end until 1923. Finally, the volume shows how the war set the stage for the collapse not only of specific empires but of the imperial world order.